Serological evidence of Rift Valley fever virus circulation in sheep and goats in Zambézia Province, Mozambique. - José Fafetine; Luis Neves; Peter N Thompson; Janusz T Paweska; Victor P M G Rutten; J A W Coetzer (Public Library of Science (PLoS), 2013)
Rift Valley fever (RVF) is endemic in most parts of Africa and has also been reported to occur in the Arabian Peninsula. It is responsible for significant morbidity and mortality, particularly in livestock, but also in humans. During the last two decades several outbreaks of RVF have been reported in countries in Southern Africa. In contrast to other countries, no clinical disease has been reported in Mozambique during this period. In a serological study conducted in 2007 in five districts of Zambézia Province, Mozambique, of a total of 654 small ruminants sampled (277 sheep and 377 goats), 35.8% of sheep sera and 21.2% of goat sera were positive for RVF virus (RVFV) antibodies in a virus neutralization test (VN) and in an IgG enzyme-linked immunosorbent assay (ELISA). In 2010, a cross-sectional survey was conducted in 313 sheep and 449 goats in two districts of the same province. This study revealed an overall seropositivity rate of 9.2% in sheep and 11.6% in goat and an increased likelihood of being seropositive in older animals (OR = 7.3; p<0.001) using an IgG ELISA. 29 out of 240 animals assessed for RVF specific IgM by ELISA were positive, suggesting recent exposure to RVFV. However, a longitudinal study carried out between September 2010 and April 2011 in a cohort of 125 of these animals (74 sheep and 51 goats) failed to demonstrate seroconversion. The results of the study indicate that RVFV circulates sub-clinically in domestic small ruminants in Zambézia Province.